Performance Analysis of Tangerang City Local Government Information System Website - Franki Slamet; Agus Munandar (Primanomics : Jurnal Ekonomi & Bisnis, 2022)
This research was conducted as a basis for performance analysis of the information system website local government of Tangerang City. It will be described on the results of measurement and assessment of the information system of the tangerang city government. Of course, government information systems are needed to improve public services. With the results of the information system of the local government of Tangerang City is well indicated.